2005
DOI: 10.1038/sj.ijir.3901324
|View full text |Cite
|
Sign up to set email alerts
|

Do sexual dysfunctions get better during dialysis? Results of a six-month prospective follow-up study from Turkey

Abstract: Dialysis improves most symptoms of end-stage renal disease (ESRD), yet many patients continue to experience sexual dysfunction (SD) during the dialysis treatment. The aim of this preliminary study was to evaluate the frequency and the course of SD during a 6-month dialysis treatment. Additionally, relationships between the level of depression, cognitive impairment and biochemical parameters of SD were also assessed. The subjects were 43 ESRD (25 male and 18 female) on dialysis treatment for at least 12 months.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 12 publications
4
34
0
Order By: Relevance
“…This finding is consistent with the results of other studies showing that SD is more frequent in patients with chronic renal disease (3,4,35,36,37,38). In a study conducted with patients undergoing dialysis treatment, 65% of participants expressed dissatisfaction with their sexual life, 40% expressed that sexual intercourse does not arouse any more interest, and 25% expressed symptoms of probable SD (39).…”
Section: Discussionsupporting
confidence: 83%
“…This finding is consistent with the results of other studies showing that SD is more frequent in patients with chronic renal disease (3,4,35,36,37,38). In a study conducted with patients undergoing dialysis treatment, 65% of participants expressed dissatisfaction with their sexual life, 40% expressed that sexual intercourse does not arouse any more interest, and 25% expressed symptoms of probable SD (39).…”
Section: Discussionsupporting
confidence: 83%
“…[1,6] Soykan et al used the Arizona Sexual Experience Scale (ASEX) and reported that sexual dysfunction was 61% in female with HD patients. [5] Basok et al using FSFI scores reported that the rates of FSD were 81, 66.7, and 50% in the PD and HD patients and control subjects, respectively. [17] We found that SD was 95.7% in female with ESRD patients (94.1% in PD; all of HD patients) and 45.8% in the control.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, little clinical research has been done on FSD; therefore, our knowledge and understanding of this disorder are limited. [2,5] We evaluated sexual function in female ESRD patients using the validated Female Sexual Function Index (FSFI) and relation with QOL, depression, and some laboratory parameters.…”
Section: Introductionmentioning
confidence: 99%
“…23 Anxiety disorders can preclude women's ability to attend to sexual stimuli and to be lost in the moment. For women with diabetes, 34 renal failure 35 or multiple sclerosis, 36 it is the comorbid depression that is associated with higher prevalence of sexual dysfunction compared to control women.…”
Section: Risk Factors For Sexual Dysfunctionmentioning
confidence: 99%